RPMB predicts the disease-free survival of head-and-neck squamous carcinoma after adjuvant concurrent radio-chemotherapy - An, Ning; Zhang, Yongchun; Lu, Haijun; Yang, Xue (Frontiers in Genetics, 2025)
PurposeCurrently, adjuvant concurrent radio-chemotherapy (ACRT) is the standard of care for head-and-neck squamous cell carcinoma (HNSC) with microscopically involved surgical margins (MISM) and/or extra-nodal extension (ENE), whereas the toxicity of cisplatin-based chemotherapy is non-negligible.MethodsIn the current study, we identified a novel biomarker, referred to as RPMB (Repair Gene Promoter Methylation Burden), with the aim of identifying the subset of HNSC patients who are likely to respond favorably to ACRT. RPMB is defined as the proportion of methylated DNA repair genes (DRGs) relative to the total number of DRGs. We obtained the methylation profiles and clinical data for 528 HNSC patients from the Cancer Genome Atlas (TCGA) database.ResultsAnalysis revealed that the DRGs in HNSC were significantly hypomethylated compared to the other genes across the entire methylation profile (all p-values <0.001). HNSCs with higher RPMB tended to be ≥70 years old, female, and with primary anatomic location of oral cavity. High RPMB was found significantly related to a poor DFS in HNSCs in subgroup analysis (HR = 1.475, p = 0.024, 95% CI: 1.053–2.065). Moreover, Kaplan-Meier analysis showed that high RPMB was significantly associated with a poor DFS in these patients who received ACRT due to MISM or ENE (HR = 2.721, 95% Cl: 1.094–6.767, p = 0.025). The median DFS for patients with lower RPMB was 2.33 years (95% CI: 1.07 to +∞ years) and median DFS for those with higher RPMB was 0.64 years (95% CI: 0.62 to +∞ years).ConclusionLow RPMB might serve as a promising indicator for identifying suitable HNSC patients who might be medically fit for ACRT.